Filament and manufacturing method thereof

The filament with controlled fiber distribution and surface treatment agents addresses the issues of modeling accuracy and strength in continuous fiber-reinforced resin composites, enhancing modeling precision and strength.

JP2025014891APending Publication Date: 2025-01-30ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023117828
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-19
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

Conventional filaments used in continuous fiber-reinforced resin composite materials have inadequate cross-sectional shapes, leading to insufficient modeling accuracy, strength, and elasticity.

Method used

The filament is designed with continuous reinforced fibers that gather in the long direction, with a specific cross-sectional shape characterized by a low FF value (0.50 or less) and a controlled fiber distribution, using a manufacturing method that includes surface treatment agents to enhance compatibility with thermoplastic resin.

Benefits of technology

The filament achieves improved modeling accuracy and high strength, with reduced filament flatness and increased elasticity, facilitating easier nozzle entry and better modeling outcomes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025014891000003
    Figure 2025014891000003
  • Figure 2025014891000004
    Figure 2025014891000004
  • Figure 2025014891000005
    Figure 2025014891000005
Patent Text Reader

Abstract

To provide a filament having good formability, capable of molding a shaped article having high strength and good molding accuracy and a manufacturing method thereof.SOLUTION: A filament for additive manufacturing includes continuous reinforcement fibers and a thermoplastic resin, has a continuous reinforcement fiber folded factor Ff calculated by the following (a)-(f) of 0.50 or under, and forms a continuous reinforcement fiber bundle by assembling 60% or over of the continuous reinforcement fibers in a cross section orthogonal to a longer direction. (a) A filament is embedded in a resin and a cross section orthogonal to a longer direction is exposed by polishing. (b) An image of the cross section is taken by a microscope. (c) The smallest circle where the whole continuous reinforcement fibers can be in is drawn in the image. (d) Distances l between points on the circumference of the circle and continuous reinforcement fibers closest to respective points are measured, and the longest l is shown as L. (e) A ratio ff of L to a length R of a diameter of the circle is calculated. (f) ff is calculated at desired 20 cross sections, and their average value is shown as Ff.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a filament and a method for producing the same. [Background technology]

[0002] Composite material molded articles in which a reinforcing material such as glass fiber is added to a matrix resin material are used for structural parts of various machines and automobiles, pressure vessels, tubular structures, etc. In particular, from the viewpoint of strength, continuous fiber reinforced resin composite materials in which the reinforcing fiber is continuous fiber are desired. In recent years, a method of laminating continuous fiber filaments made of continuous fiber reinforced resin using a 3D printer or the like has attracted attention as a molding method for continuous fiber reinforced resin composite materials. The method of laminating continuous fiber filaments is being developed because it does not require a mold and has a high degree of freedom in shape. For the continuous fiber filaments used in this case, there have been proposals for improving the circularity of the filaments or the dispersion of the continuous reinforcing fibers in the filaments (for example, Patent Document 1), and for improving the thermoplastic resin contained therein (for example, Patent Document 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2020-217929 [Patent Document 2] International Publication No. 2019-195694 Summary of the Invention [Problem to be solved by the invention]

[0004] However, in all of the filaments of the prior art, the cross-sectional shape of the continuous reinforcing fibers contained therein is not good, and there is room for improvement in terms of the moldability when using the filaments in a 3D printer, and the physical properties of the obtained molded products, such as their strength and elastic modulus, which are insufficient.

[0005] In view of the state of the art, the problem that the present invention aims to solve is to provide a filament and a manufacturing method thereof that have good shapeability and can be used to form shaped products having high strength and good shape accuracy. [Means for solving the problem]

[0006] The inventors conducted intensive research and repeated experiments to solve these problems, and unexpectedly discovered that the above problems could be solved by devising the cross-sectional shape of the bundle of continuous reinforcing fibers contained in the filament, which led to the completion of the present invention.

[0007] That is, the present invention is as follows. [1] A filament for additive manufacturing comprising continuous reinforcing fibers and a thermoplastic resin, characterized in that the degree of continuous reinforcing fiber folding (Ff) obtained by the following steps (a) to (f) is 0.50 or less, and in a cross section perpendicular to the longitudinal direction of the filament, 60% or more of the continuous reinforcing fibers are gathered together to form a continuous reinforcing fiber bundle. (a) The filament is embedded in a resin, and a cross section perpendicular to the longitudinal direction is exposed by polishing. (b) An image of the cross section is taken using a microscope. (c) In the obtained image, the smallest circle that can contain all of the continuous reinforcing fibers is drawn. (d) The distance l between each point on the circumference of the circle and the continuous reinforcing fiber closest to each point is measured, and the longest distance l is designated as L. (e) The ratio ff of L to the diameter R of the circle is calculated using the following formula (1). ff=L / R (1) (f) ff is calculated for any 20 cross sections, and the average value is Ff. [2] The filament according to [1], wherein the maximum value of ff among the 20 cross sections is 0.50 or less. [3] The filament according to [1] or [2], wherein the fiber volume content of the filament is 5 to 50%. [4] The filament according to any one of [1] to [3], having a continuous reinforcing fiber dispersion coefficient (Fd) of 3 or less, which is determined by the following steps (A) to (F). (A) The filament is embedded in resin, and a cross section perpendicular to the longitudinal direction is exposed by polishing. (B) An image of the cross section is taken using a microscope. (C) In the obtained image, the smallest circle that can contain all of the continuous reinforcing fibers is drawn. (D) Among the diameters of the circles, the diameter that crosses the continuous reinforcing fiber bundle the greatest number of times is determined. (E) The number of times that the diameter that crosses the continuous reinforcing fiber bundle the most crosses the continuous reinforcing fiber bundle is defined as fd. (F)fd is calculated for 20 arbitrary cross sections, and the average value is taken as Fd. [5] The filament according to any one of [1] to [4], wherein in the cross section, the width of the continuous reinforcing fiber bundle is 3 to 20 times the fiber diameter of the continuous reinforcing fiber. [6] The filament according to any one of [1] to [5], wherein in the cross section, the length of the continuous reinforcing fiber bundle is three times or more the width of the continuous reinforcing fiber bundle. [7] The filament according to any one of [1] to [6], wherein the continuous reinforcing fibers contain a surface treatment agent, and the difference in SP value between the thermoplastic resin and the surface treatment agent of the continuous reinforcing fibers is 1.0 or less. [8] A method for producing a filament according to any one of [1] to [6], treating the continuous reinforcing fibers with a surface treatment agent to produce continuous reinforcing fibers that include a surface treatment agent; A method for producing a filament, wherein the difference in SP value between the surface treatment agent for the continuous reinforcing fiber and the thermoplastic resin is 1.0 or less. Effect of the Invention

[0008] According to the present invention, it is possible to provide a filament and a manufacturing method thereof that have good shapeability and can be used to form shaped articles having high strength and good shape accuracy. [Brief description of the drawings]

[0009] [Figure 1] FIG. 2 is a schematic cross-sectional view showing an example of a filament of the present embodiment. [Diagram 2] 1A and 1B are schematic cross-sectional views of a filament, illustrating each point on the circumference of the smallest circle that can contain all of the continuous reinforcing fibers, the distance l from each point to the nearest continuous reinforcing fiber, and L, which is the longest distance l. [Diagram 3] 1A is a schematic cross-sectional view showing the shape of an example of a filament according to the present embodiment before and after shaping, and FIG. 1B is a schematic cross-sectional view showing the shape of an example of a conventional filament before and after shaping. [Figure 4] 1(a) and (b) are schematic cross-sectional views of a filament, illustrating the number of times the diameter of the smallest circle that can contain all of the continuous reinforcing fibers crosses the continuous reinforcing fiber bundle. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, an embodiment of the present invention (hereinafter, referred to as the present embodiment) will be described in detail. Note that the present invention is not limited to the following embodiment, and can be practiced in various modifications within the scope of the gist of the present invention.

[0011] [filament] The filament of this embodiment is for additive manufacturing, contains continuous reinforcing fibers and a thermoplastic resin, has a continuous reinforcing fiber folding degree (Ff) of 0.50 or less, as determined by the following steps (a) to (f), and in a cross section perpendicular to the longitudinal direction of the filament (hereinafter simply referred to as a "transverse cross section"), 60% or more of the continuous reinforcing fibers are gathered together to form a continuous reinforcing fiber bundle. (a) The filament is embedded in resin and then polished to expose the cross section perpendicular to the longitudinal direction (cross section). (b) An image of the cross section exposed in (a) is taken using a microscope. (c) In the image obtained in (b), draw the smallest circle that can contain all of the continuous reinforcing fibers. (d) For each point on the circumference of the circle drawn in (c), measure the shortest distance l to the continuous reinforcing fiber bundle, and the longest distance l is taken as L. (e) Calculate the ratio ff of L to the diameter R of the circle using the following formula (1). ff=L / R (1) (f) ff is calculated for any 20 cross sections, and the average value is Ff.

[0012] In this disclosure, "additive manufacturing" refers to a process of building three-dimensional objects by incrementally adding (building up) layers of material, as opposed to subtractive manufacturing, typically through machining. In addition, in the present disclosure, the term "continuous reinforcing fiber bundle" refers to an aggregate formed by assembling 60% or more of the continuous reinforcing fibers when the total number of the continuous reinforcing fibers is taken as 100% when observing the cross section of the filament. In the image of the cross section of the filament, when a circle having a diameter three times the fiber diameter of each continuous reinforcing fiber is drawn with the center of the continuous reinforcing fiber as the center of the circle, if three or more other continuous reinforcing fibers are included in the circle, the continuous reinforcing fiber is included in the continuous reinforcing fiber bundle (forms an aggregate). For example, the filament shown in FIG. 1 is an example of a filament in which the aggregate of continuous reinforcing fibers surrounded by a dashed line is a continuous reinforcing fiber bundle, and there are two continuous reinforcing fibers that are not included in the continuous reinforcing fiber bundle. The ratio of the continuous reinforcing fibers included in the continuous reinforcing fiber bundle is preferably 70% or more, more preferably 80% or more, when the total number of the continuous reinforcing fibers is taken as 100%. The upper limit of the ratio of the continuous reinforcing fibers is not particularly limited, and may be, for example, 100% or less, or 90% or less. In addition, in the present disclosure, the "smallest circle that can contain all the continuous reinforcing fibers" is the circle that has the smallest diameter among the circles drawn to contain all the continuous reinforcing fibers in the image of the cross section of the filament. In other words, it is the circumscribing circle of the outline of the continuous reinforcing fibers drawn to contain all the continuous reinforcing fibers in the image of the cross section of the filament. Therefore, for example, as shown in Figures 2(a) and (b), the smallest circle that can contain all the continuous reinforcing fibers contains not only the continuous reinforcing fibers contained in the continuous reinforcing fiber bundle, but also all the continuous reinforcing fibers not contained in the continuous reinforcing fiber bundle. Additionally, in this disclosure, "each point on the circumference of a circle" refers to each and every point on the circumference of a circle.

[0013] More specifically, the degree of folding of the continuous reinforcing fibers (Ff) can be calculated by, for example, drawing a circle in which all the continuous reinforcing fibers are contained in the image of the cross section of the filament, as shown in Figures 2(a) and (b), and measuring the diameter R of the circle and the shortest distance l from each point on the circumference of the circle to the continuous reinforcing fiber bundle (only three points including L, the longest l, are shown in the figure). Ff is a parameter indicating the degree of folding of the cross-sectional shape of the continuous reinforcing fiber bundle, and the more it is folded, the smaller the value of Ff becomes. For example, Figures 2(a) and (b) show filaments containing approximately the same number of continuous reinforcing fibers, but the cross-sectional shape of the continuous reinforcing fiber bundle in the filament in Figure 2(a) is more folded than that in the filament in Figure 2(b), and the Ff value of the filament in Figure 2(a) is smaller than that of the filament in Figure 2(b).

[0014] The continuous reinforcing fiber folding degree (Ff) is preferably 0.45 or less, more preferably 0.40 or less, even more preferably 0.35 or less, even more preferably 0.30 or less, even more preferably 0.25 or less, and particularly preferably 0.20 or less. When the continuous reinforcing fiber is bundled and the continuous reinforcing fiber folding degree (Ff) is within the above range, the cross-sectional shape of the filament is easily controlled, the flatness of the filament cross section is reduced, and it is easy to enter the nozzle of a 3D printer or the like. Therefore, the filament has good moldability, and the molding accuracy of the obtained molded product is good. In addition, as shown in FIG. 3, the filament of this embodiment (FIG. 3(a)) is in a state where the continuous reinforcing fiber bundle is folded before molding, so that the continuous reinforcing fiber bundle spreads and disperses throughout the filament during molding, and the cross-sectional shape of the filament is easily flattened (the filament is easily crushed). On the other hand, the conventional filament (FIG. 3(b)) contains approximately the same number of continuous reinforcing fibers as the filament of this embodiment (FIG. 3(a)), but since the continuous reinforcing fibers are dispersed throughout the filament before molding, it has high strength and the cross-sectional shape of the filament is less likely to be flattened during molding (the filament is less likely to be crushed). Therefore, the product made from the filament of this embodiment has smaller gaps between the filaments, which are likely to become the starting point of destruction, than the product made from the conventional filament, and can exhibit excellent strength and elastic modulus.

[0015] Methods for adjusting the degree of folding of the continuous reinforcing fibers (Ff) within the above range include, for example, a method of matching the SP values ​​of the surface treatment agent contained in (attached to) the continuous reinforcing fibers and the thermoplastic resin, i.e., a method of reducing the difference in the SP values ​​between the surface treatment agent and the thermoplastic resin, and a method of physically folding the continuous reinforcing fibers after opening them during filament production.

[0016] If the difference in SP value between the surface treatment agent and the thermoplastic resin is small, the surface treatment agent of the continuous reinforcing fibers dissolves appropriately in the thermoplastic resin, and the continuous reinforcing fibers tend to be folded after being appropriately opened. The difference in SP value between the surface treatment agent for the continuous reinforcing fiber and the thermoplastic resin is preferably 1.3 or less, more preferably 1.0 or less, even more preferably 0.7 or less, even more preferably 0.4 or less, particularly preferably 0.1 or less, and most preferably 0.05 or less. The difference in SP value may be the absolute value of the difference between the SP value of the surface treatment agent for the continuous reinforcing fibers and the SP value of the thermoplastic resin. The SP value can be measured by the method described in the Examples below.

[0017] The maximum value of the ff obtained for the above 20 cross sections is preferably 0.50 or less, more preferably 0.45 or less, even more preferably 0.40 or less, even more preferably 0.35 or less, even more preferably 0.30 or less, and particularly preferably 0.25 or less. When ff is within the above range, it becomes easy to control the cross-sectional shape of the filament, and the flatness of the filament cross section becomes small, making it easier to enter the nozzle of a 3D printer or the like, so that the moldability is good and the molding accuracy of the obtained molded product tends to be good.

[0018] In step (a), the method for embedding the filament in the resin is not particularly limited, but examples thereof include the following methods. First, the filament is cut to a length of 15 to 25 mm. An acrylic plate of 4 to 6 mm square and 15 to 25 mm long is prepared, and the cut filament is attached to the acrylic plate in a straightened state. Next, the acrylic plate with the filament attached is placed on the flat surface of a glass plate so that the length direction of the acrylic plate is perpendicular to the flat surface of the glass plate, and fixed using double-sided tape or the like. Next, an acrylic pipe having a length of about the same as the acrylic plate and an inner diameter (for example, 13 to 15 mm) large enough to contain the acrylic plate is prepared, and the acrylic pipe is placed on the flat surface of the glass plate so that the acrylic plate with the filament attached is the center (axis) of the acrylic pipe and surrounds the acrylic plate. An embedding resin (epoxy resin, etc.) is injected into the acrylic pipe without allowing air to enter, and the embedding resin is hardened. More specifically, resin embedding can be carried out by the method described in the Examples below.

[0019] In step (a), the method of polishing the resin-embedded filament to expose a cross section perpendicular to the longitudinal direction (cross section exposure method) is not particularly limited, and can be performed using a polishing machine. For example, a polishing surface can be polished with a force of 35 to 350 g / cm while being careful not to damage the filament. 2 It is preferable to perform polishing under conditions in which a force of 0.1 to 100 MPa is applied. More specifically, the cross-section can be carried out by the method and conditions described in the Examples below.

[0020] In step (b), the method of photographing the cross section of the filament exposed in step (a) with a microscope to obtain an image is not particularly limited, and the image may be photographed at a magnification that allows an image including the entire cross section of the exposed filament to be obtained. For example, it is preferable to photograph at a magnification of 300 to 400 times, or at a magnification where the length and width of the observed image are both within the range of 3 to 5 mm.

[0021] The fiber volume fraction (Vf) of the filament, which is the volume ratio of the continuous reinforcing fibers to the filament, is preferably 5 to 50%, more preferably 10 to 40%, and even more preferably 15 to 35%. When the fiber volume fraction (Vf) of the filament is in the above range, the moldability is good, and the molding precision of the obtained shaped product tends to be good. The fiber volume content (Vf) of the filament can be determined, for example, by burning off the resin contained in the filament in an electric furnace and measuring the mass of the remaining reinforcing fibers to determine the masses of the reinforcing fibers and resin contained in the filament, and then dividing the obtained masses of the reinforcing fibers and the mass of the resin by their respective densities to convert them into volumes.

[0022] The filament of this embodiment preferably has a continuous reinforcing fiber dispersion coefficient (Fd) of 3 or less, which is determined by the following steps (A) to (F). (A) The filament is embedded in resin and then polished to expose a cross section perpendicular to the longitudinal direction (cross section). (B) An image of the cross section exposed in (A) is taken using a microscope. (C) In the image obtained in (B), the smallest circle that can contain all of the continuous reinforcing fibers is drawn. (D) Of the diameters of the circles drawn in (C), determine the diameter that crosses the continuous reinforcing fiber bundle the most number of times. (E) The number of times that the diameter that crosses the continuous reinforcing fiber bundle determined in (D) crosses the continuous reinforcing fiber bundle is defined as fd. (F)fd is calculated for 20 arbitrary cross sections, and the average value is taken as Fd.

[0023] More specifically, the continuous reinforcing fiber dispersion coefficient (Fd) can be obtained by drawing the smallest circle that contains all the continuous reinforcing fibers in the cross-sectional image of the filament, and calculating the number of times the circle crosses the continuous reinforcing fiber bundle for the entire diameter, as shown in Figures 4(a) and 4(b). In Figures 4(a) and 4(b), the parts (line segments) where the diameter of the circle crosses the continuous reinforcing fiber bundle are shown with thick lines. The steps (A) and (B) can be carried out in the same manner as the steps (a) and (b) for determining the degree of folding of the continuous reinforcing fibers (Ff) described above.

[0024] The continuous reinforcing fiber dispersion coefficient (Fd) of the filament is more preferably 2.8 times or less, even more preferably 2.6 times or less, even more preferably 2.4 times or less, and particularly preferably 2.2 times or less. When the continuous reinforcing fiber dispersion coefficient (Fd) of the filament is in the above range, the moldability is good, and the molded product obtained tends to have good molding accuracy. In addition, the continuous reinforcing fiber bundles tend to spread easily during molding, which reduces the gaps between the filaments, and the obtained molded product tends to exhibit excellent strength and elastic modulus.

[0025] In the filament of this embodiment, the width of the continuous reinforcing fiber bundle in the cross section of the filament is preferably 3 to 30 times, more preferably 3 to 20 times, and even more preferably 4 to 15 times the fiber diameter of the continuous reinforcing fiber. In the present disclosure, the "width of the continuous reinforcing fiber bundle" is determined by measuring the distance between any 20 points on the contour line of the continuous reinforcing fiber bundle in the image of the cross section of the filament and another point where the perpendicular line of each point intersects with the contour line (the length of the line segment obtained by cutting the perpendicular line of each point by the contour line, with each point as one end), and the average of the measured values ​​is determined as the width of the continuous reinforcing fiber bundle in that cross section. The average value obtained by measuring five arbitrary cross sections is determined as the width of the continuous reinforcing fiber bundle of that filament. The arbitrary 20 points may be, for example, the points dividing the contour line of the continuous reinforcing fiber bundle into 19 points of approximately equal length. In the present disclosure, the "fiber diameter of the continuous reinforcing fiber" refers to the fiber diameter of any 20 continuous reinforcing fibers included in the continuous reinforcing fiber bundle in an image of a cross section of a filament, and the average of the measured values ​​is the fiber diameter of the continuous reinforcing fiber in that cross section. The average value of measurements at any 5 cross sections is the fiber diameter of the continuous reinforcing fiber of that filament.

[0026] In the filament of this embodiment, the length of the continuous reinforcing fiber bundle in the cross section of the filament is preferably at least twice, more preferably at least three times, and even more preferably at least five times, the width of the continuous reinforcing fiber bundle. The upper limit is not particularly limited, but for example, the length of the continuous reinforcing fiber bundle may be 1000 times or less, 500 times or less, or 100 times or less, the width of the continuous reinforcing fiber bundle. In this disclosure, the "length of the continuous reinforcing fiber bundle" is defined as half (1 / 2) of the length of the outline of the continuous reinforcing fiber bundle. The average value measured at any five cross sections is defined as the length of the continuous reinforcing fiber bundle of that filament.

[0027] The shape of the filament in this embodiment is not limited to the following, but for example, the cross section perpendicular to the longitudinal direction of the filament may be circular or approximately circular (eg, elliptical). Moreover, the length of the filament in the longitudinal direction is preferably 1 m or more, more preferably 10 m or more, and even more preferably 100 m or more. The diameter of the filament is preferably 0.1 to 3.0 mm, more preferably 0.2 to 2.0 mm, and further preferably 0.3 to 1.5 mm. When the cross section perpendicular to the longitudinal direction of the filament is a substantially circular shape such as an ellipse, the maximum diameter may be regarded as the diameter of the filament.

[0028] The impregnation rate of the filament in this embodiment is not particularly limited, but is preferably 40% or more, more preferably 60% or more, even more preferably 80% or more, and even more preferably 90% or more. The upper limit of the impregnation rate is not particularly limited, and may be, for example, 99% or less. The impregnation rate can be calculated by determining the area of ​​the region surrounded by the outline of the continuous reinforcing fiber bundle in an image of a cross section perpendicular to the longitudinal direction of the filament, and the area of ​​voids contained in the region surrounded by the outline of the continuous reinforcing fiber bundle, and using the following formula. Impregnation rate (%) = {1-(area of ​​voids / area of ​​area enclosed by the outline of continuous reinforcing fiber bundle)} x 100 The average of the impregnation rates calculated for the five cross sections may be regarded as the impregnation rate of the filament.

[0029] [Filament manufacturing method] The filament of this embodiment can be produced, for example, by passing the continuous reinforcing fiber through a molten thermoplastic resin. At this time, the continuous reinforcing fiber may be opened in the width direction, and the opened continuous reinforcing fiber may be folded after contact with the molten thermoplastic resin, or may be folded before contact with the molten thermoplastic resin. Examples of methods for opening the continuous reinforcing fiber in the width direction include a method of squeezing the fiber with a roller or a rod while applying heat, a method of opening the fiber with ultrasonic waves, and a method of opening the fiber by applying air. As a method for impregnating the continuous reinforcing fibers with the molten thermoplastic resin, for example, pressure may be applied to the width direction or thickness of the continuous reinforcing fibers when the continuous reinforcing fibers are passed through the molten thermoplastic resin. Examples of the method for applying pressure include a method of squeezing the continuous reinforcing fibers with multiple rods and a method of increasing the pressure of the molten resin.

[0030] The temperature of the molten resin is not limited to the following, but is preferably a temperature at which the viscosity of the thermoplastic resin is 10 g / 10 min or more, more preferably a temperature at which the viscosity is 30 g / 10 min or more, even more preferably a temperature at which the viscosity is 50 g / 10 min or more, and even more preferably a temperature at which the viscosity is 100 g / 10 min or more. The temperature of the molten resin is preferably a temperature at which the viscosity of the thermoplastic resin is 1000 g / 10 min or less, more preferably a temperature at which the viscosity is 500 g / 10 min or less, and even more preferably a temperature at which the viscosity is 300 g / 10 min or less.

[0031] [Continuous reinforcing fiber] The term "continuous reinforcing fibers" refers to reinforcing fibers that are substantially uninterrupted in the filament. In this disclosure, "substantially uninterrupted" refers to a state in which continuous reinforcing fibers are included in all cross sections perpendicular to the longitudinal direction of the filament. In addition, it is ideal for all of the reinforcing fiber single threads within the filament to be uninterrupted, but if 80% or more of the single threads are uninterrupted for 1 m on one or both sides from any point along the longitudinal direction of the filament, they may be considered continuous.

[0032] As the continuous reinforcing fibers, those used in ordinary continuous fiber reinforced resin composite materials may be used. Examples of continuous reinforcing fibers include, but are not limited to, glass fibers, carbon fibers, vegetable fibers, aramid fibers, ultra-high strength polyethylene fibers, polybenzazole fibers, liquid crystal polyester fibers, polyketone fibers, metal fibers, and ceramic fibers. From the viewpoints of mechanical properties, thermal properties, and versatility, glass fibers, carbon fibers, vegetable fibers, and aramid fibers are preferred. The continuous reinforcing fibers may be used alone or in combination of two or more.

[0033] The continuous reinforcing fibers may be treated with a surface treatment agent (preferably a sizing agent described below).

[0034] -Bundling agent- The continuous reinforcing fibers preferably have a sizing agent attached thereto. The sizing agent may include one or more selected from the group consisting of a coupling agent (for example, a silane coupling agent), a lubricant, and a binder. The sizing agent may be comprised of a coupling agent and a binder, or may be comprised of a coupling agent, a lubricant, and a binder. By using a sizing agent that creates a strong bond between the continuous reinforcing fibers and the resin that coats them, filaments with low voids can be obtained. Sizing agents may be added externally to the materials used or may be included internally in the materials used, for example, lubricants may be included in the commercial product of the thermoplastic resin used, and coupling agents may be included on the surface of continuous reinforcing fibers (e.g., carbon fibers).

[0035] Coupling agents are compounds that bond materials with different properties, mainly inorganic and organic materials. Examples of coupling agents include, but are not limited to, silane coupling agents, polymer coupling agents, and polymerizable coupling agents.

[0036] --Silane coupling agent-- Silane coupling agents are usually used as surface treatment agents for continuous reinforcing fibers (for example, glass fibers and carbon fibers) and contribute to improving the interfacial adhesive strength. Examples of silane coupling agents include, but are not limited to, aminosilanes such as γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, and N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane; mercaptosilanes such as γ-mercaptopropyltrimethoxysilane and γ-mercaptopropyltriethoxysilane; epoxysilanes; vinylsilanes, maleic acids, etc. When using polyamide as the thermoplastic resin, it is preferable to select one that is easily bonded to the carboxyl group or amino group that is the terminal group of the polyamide resin, and aminosilanes are preferred. Examples of the polymer coupling agent include, but are not limited to, diamines, polycarboxylic acids, and epoxies. From the viewpoint of compatibility with thermoplastic resins, diamines and polycarboxylic acids are preferred. Examples of the polymerizable coupling agent include, but are not limited to, epoxies, phenols, ethers, lactones, etc., and from the viewpoint of compatibility with thermoplastic resins, phenols and lactones are preferred.

[0037] --Lubricant-- The lubricant contributes to improving the opening property of continuous reinforcing fibers (for example, glass fibers). As the lubricant, any ordinary liquid or solid lubricating material can be used depending on the purpose, so long as it does not interfere with the silane coupling agent and the binder. Examples of the lubricant include, but are not limited to, animal, vegetable or mineral waxes such as carnauba wax and lanolin wax; surfactants such as fatty acid amides, fatty acid esters, fatty acid ethers, aromatic esters, and aromatic ethers.

[0038] --Binding agent-- The binder contributes to improving the bundling property of continuous reinforcing fibers (for example, carbon fibers or glass fibers) and / or improving the interfacial adhesive strength.

[0039] As the binder, a polymer according to the purpose, or a thermoplastic resin other than the thermoplastic resin as the main material of the filaments can be used. Examples of the polymer as a binder include, but are not limited to, homopolymers of acrylic acid, copolymers of acrylic acid and other copolymerizable monomers, copolymers of acrylic acid esters and / or methacrylic acid esters and copolymerizable monomers, and salts of these with primary, secondary, and tertiary amines, etc. In addition, polyurethane resins synthesized from isocyanates such as m-xylylene diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), and isophorone diisocyanate, and polyester or polyether diols, are also preferably used. The homopolymer of acrylic acid preferably has a weight average molecular weight of 1,000 to 90,000, and more preferably 1,000 to 25,000. The copolymerizable monomer constituting the copolymer of acrylic acid and other copolymerizable monomers is not limited to the following, but may be, for example, one or more selected from the group consisting of acrylic acid, maleic acid, methacrylic acid, vinylacetic acid, crotonic acid, isocrotonic acid, fumaric acid, itaconic acid, citraconic acid, and mesaconic acid, among monomers having a hydroxyl group and / or a carboxyl group (excluding the case where only acrylic acid is used). It is preferable to have one or more ester monomers as the copolymerizable monomer. Examples of salts of acrylic acid homopolymers and copolymers with primary, secondary and tertiary amines include, but are not limited to, triethylamine salts, triethanolamine salts, glycine salts, etc. The degree of neutralization is preferably 20 to 90%, more preferably 40 to 60%, from the viewpoints of improving the stability of a mixed solution with other concomitant chemicals (such as a silane coupling agent) and reducing the amine odor. The weight average molecular weight of the acrylic acid polymer that forms the salt is not particularly limited, but is preferably in the range of 3,000 to 50,000. From the viewpoint of improving the bundling property of continuous reinforcing fibers (e.g., glass fibers), it is preferably 3,000 or more, and from the viewpoint of improving the properties when made into a composite molded product, it is preferably 50,000 or less. When polyamide is used as the thermoplastic resin, it is preferable to use a resin having good wettability or surface tension similar to that of the polyamide resin as the binder. Specifically, for example, an emulsion of a polyurethane resin, an emulsion of a polyamide resin, or a modified product thereof can be selected.

[0040] Thermoplastic resins used as binders include, but are not limited to, polyolefin resins, polyamide resins, polyurethane resins, polyacetal resins, polycarbonate resins, polyester resins, polyether ketones, polyether ether ketones, polyether sulfones, polyphenylene sulfide, thermoplastic polyetherimides, thermoplastic fluorine resins, and modified thermoplastic resins obtained by modifying these resins. If the thermoplastic resin used as the binder is the same type of thermoplastic resin and / or modified thermoplastic resin as the resin that covers the periphery of the continuous reinforcing fibers, the adhesiveness between the glass fibers and the thermoplastic resin is improved after the composite material is formed, which is preferable.

[0041] Furthermore, from the viewpoint of further improving the adhesion between the continuous reinforcing fibers and the thermoplastic resin coating them, and reducing the proportion of emulsifier components or eliminating the need for emulsifier when the bundling agent is attached to the continuous reinforcing fibers (e.g., glass fibers or carbon fibers) as an aqueous dispersion, modified thermoplastic resins are preferred as the thermoplastic resin used as the binder. The modified thermoplastic resin used herein means a thermoplastic resin obtained by copolymerizing a different monomer component other than a monomer component capable of forming the main chain of the thermoplastic resin, for the purpose of changing the properties of the thermoplastic resin, thereby modifying the hydrophilicity, crystallinity, thermodynamic properties, etc. The modified thermoplastic resin used as the binder is not limited to the following, but examples thereof include modified polyolefin resins, modified polyamide resins, modified polyester resins, and the like.

[0042] The modified polyolefin resin as a binder is a copolymer of an olefin monomer such as ethylene or propylene with a monomer copolymerizable with the olefin monomer, such as an unsaturated carboxylic acid and / or an ester thereof, or a homopolymer of a monomer copolymerizable with the olefin monomer, such as an unsaturated carboxylic acid and / or an ester thereof, and can be produced by a known method. It may be a random copolymer in which an olefin monomer is copolymerized with an unsaturated carboxylic acid and / or an ester thereof, or a graft copolymer in which an unsaturated carboxylic acid is grafted onto an olefin. Examples of olefin monomers include, but are not limited to, ethylene, propylene, 1-butene, etc. These may be used alone or in combination of two or more. Examples of monomers copolymerizable with the olefin monomer include unsaturated carboxylic acids such as acrylic acid, maleic acid, maleic anhydride, methacrylic acid, vinylacetic acid, crotonic acid, isocrotonic acid, fumaric acid, itaconic acid, citraconic acid, and mesaconic acid, and esters of these unsaturated carboxylic acids (methyl esters, ethyl esters, and the like). These may be used alone or in combination of two or more. When the modified polyolefin resin is a copolymer of an olefin monomer and a monomer copolymerizable with the olefin monomer, the monomer ratio is preferably 60-95% by mass of the olefin monomer and 5-40% by mass of the monomer copolymerizable with the olefin monomer, and more preferably 70-85% by mass of the olefin monomer and 15-30% by mass of the monomer copolymerizable with the olefin monomer, with the total mass of the copolymer being 100% by mass. If the olefin monomer is 60% by mass or more, the affinity with the matrix is ​​good, and if the mass% of the olefin monomer is 95% by mass or less, the water dispersibility of the modified polyolefin resin is good, and it is easy to apply it uniformly to the continuous reinforcing fiber.

[0043] The modified polyolefin resin used as a binder may have modified groups such as carboxyl groups introduced by copolymerization neutralized with a basic compound. Examples of basic compounds include, but are not limited to, alkalis such as sodium hydroxide and potassium hydroxide; ammonia; and amines such as monoethanolamine and diethanolamine. The weight average molecular weight of the modified polyolefin resin used as a binder is not particularly limited, but is preferably 5,000 to 200,000, and more preferably 50,000 to 150,000. From the viewpoint of improving the bundling property of continuous reinforcing fibers (e.g., carbon fibers and glass fibers), it is preferably 5,000 or more, and from the viewpoint of emulsion stability when it is made water dispersible, it is preferably 200,000 or less.

[0044] The modified polyamide resin used as the binder is a modified polyamide compound having a hydrophilic group such as a polyalkylene oxide chain or a tertiary amine component introduced into the molecular chain, and can be produced by a known method. When a polyalkylene oxide chain is introduced into the molecular chain, for example, polyethylene glycol or polypropylene glycol partially or entirely modified with a diamine or dicarboxylic acid is copolymerized, and when a tertiary amine component is introduced, for example, aminoethylpiperazine, bisaminopropylpiperazine, α-dimethylaminoε-caprolactam, etc. are copolymerized.

[0045] The modified polyester resin used as the binder is a copolymer of a polycarboxylic acid or an anhydride thereof and a polyol, and has a hydrophilic group in the molecular skeleton including the terminals, and can be produced by a known method. Examples of the hydrophilic group include a polyalkylene oxide group, a sulfonate, a carboxyl group, and neutralized salts thereof. Examples of the polycarboxylic acid or anhydride thereof include an aromatic dicarboxylic acid, a sulfonate-containing aromatic dicarboxylic acid, an aliphatic dicarboxylic acid, an alicyclic dicarboxylic acid, a trifunctional or higher polycarboxylic acid, and the like. Examples of aromatic dicarboxylic acids include, but are not limited to, phthalic acid, terephthalic acid, isophthalic acid, orthophthalic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, and phthalic anhydride. Examples of sulfonate-containing aromatic dicarboxylic acids include, but are not limited to, sulfoterephthalate, 5-sulfoisophthalate, and 5-sulfoorthophthalate. Examples of the aliphatic dicarboxylic acid or alicyclic dicarboxylic acid include, but are not limited to, fumaric acid, maleic acid, itaconic acid, succinic acid, adipic acid, azelaic acid, sebacic acid, dimer acid, 1,4-cyclohexanedicarboxylic acid, succinic anhydride, and maleic anhydride. Examples of tri- or higher functional polycarboxylic acids include, but are not limited to, trimellitic acid, pyromellitic acid, trimellitic anhydride, pyromellitic anhydride, and the like.

[0046] Among these, from the viewpoint of improving the heat resistance of the modified polyester resin, it is preferable that 40 to 99 mol % of the total polycarboxylic acid components are aromatic dicarboxylic acids, and from the viewpoint of emulsion stability when the modified polyester resin is made into an aqueous dispersion, it is preferable that 1 to 10 mol % of the total polycarboxylic acid components are sulfonate-containing aromatic dicarboxylic acids.

[0047] Examples of the polyol constituting the modified polyester resin include diols and tri- or higher functional polyols. Examples of diols include, but are not limited to, ethylene glycol, diethylene glycol, polyethylene glycol, propylene glycol, polypropylene glycol, polybutylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, polytetramethylene glycol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, bisphenol A or an alkylene oxide adduct thereof, etc. Examples of trifunctional or higher polyols include trimethylolpropane, glycerin, pentaerythritol, etc.

[0048] The copolymerization ratio of the polycarboxylic acid or its anhydride and the polyol constituting the modified polyester resin is preferably 40 to 60 mass% of the polycarboxylic acid or its anhydride and 40 to 60 mass% of the polyol, and more preferably 45 to 55 mass% of the polycarboxylic acid or its anhydride and 45 to 55 mass% of the polyol, relative to 100 mass% of the total mass of the copolymerization components. The weight average molecular weight of the modified polyester resin is preferably 3,000 to 100,000, and more preferably 10,000 to 30,000. From the viewpoint of improving the bundling property of continuous reinforcing fibers (e.g., carbon fibers or glass fibers), it is preferably 3,000 or more, and from the viewpoint of emulsion stability when it is made water-dispersible, it is preferably 100,000 or less.

[0049] The polymer or thermoplastic resin used as the binder may be used alone or in combination of two or more kinds. With the total amount of the binder taken as 100% by mass, it is preferable to use at least one polymer selected from homopolymers of acrylic acid, copolymers of acrylic acid and other copolymerizable monomers, copolymers of acrylic acid esters and / or methacrylic acid esters and copolymerizable monomers, and salts of these with primary, secondary, and tertiary amines, and the like, in an amount of 50% by mass or more, and more preferably 60% by mass or more.

[0050] When the sizing agent is composed of a silane coupling agent and a binder, the sizing agent is attached in a total amount of 0.1 to 3 mass%, more preferably 0.2 to 2 mass%, and even more preferably 0.2 to 1 mass% based on 100 mass% of continuous reinforcing fibers (e.g., glass fibers) as the total amount of the silane coupling agent and the binder. From the viewpoint of controlling the bundling property of the continuous reinforcing fibers (e.g., carbon fibers and glass fibers) and improving the interfacial adhesive strength, the amount of the sizing agent attached is preferably 0.1 mass% or more based on 100 mass% of the continuous reinforcing fibers (e.g., carbon fibers and glass fibers) as the total amount of the silane coupling agent and the binder, and from the viewpoint of the handleability of the yarn, is preferably 3 mass% or less. When the sizing agent is composed of a silane coupling agent, a lubricant, and a binder, the sizing agent is applied and attached in a total mass (total attached mass ratio) of the silane coupling agent, the lubricant, and the binder, preferably 0.1 to 3 mass%, more preferably 0.2 to 2 mass%, and even more preferably 0.2 to 1 mass%, based on 100 mass% of the continuous reinforcing fibers (e.g., carbon fibers or glass fibers). The total attached mass ratio is preferably 0.01 to 0.3 mass%, more preferably 0.02 to 0.2 mass%, and even more preferably 0.03 to 0.15 mass%. From the viewpoint of controlling the bundling property of the continuous reinforcing fibers (e.g., carbon fibers or glass fibers) and improving the interfacial adhesive strength, the amount of the sizing agent attached is preferably 0.01% by mass or more, and more preferably 0.1% by mass or more, as the total mass of the silane coupling agent, lubricant and binder, relative to 100% by mass of the continuous reinforcing fibers (e.g., carbon fibers or glass fibers); from the viewpoint of yarn handleability, it is preferably 3% by mass or less, and more preferably 0.3% by mass or less.

[0051] The amount of the coupling agent attached is preferably 0.05 to 1 mass %, and more preferably 0.1 to 0.9 mass %, relative to 100 mass % of the continuous reinforcing fibers.

[0052] --Use of sizing agent-- The sizing agent may be prepared in any form, such as an aqueous solution, a colloidal dispersion, or an emulsion using an emulsifier, depending on the mode of use. From the viewpoints of improving the dispersion stability and heat resistance of the sizing agent, however, it is preferably in the form of an aqueous solution. The continuous reinforcing fibers constituting the filaments of this embodiment can be obtained continuously by applying the above-mentioned sizing agent to continuous reinforcing fibers using a known method such as a roller-type applicator in a known manufacturing process, and then drying the continuous reinforcing fibers. The sizing agent for continuous reinforcing fibers can be used in a manner in which the continuous reinforcing fibers are immersed in a liquid containing the sizing agent, or in which a continuous reinforcing fiber substrate is immersed in a liquid containing the sizing agent.

[0053] Similarly, when carbon fibers are selected as the continuous reinforcing fibers, a sizing agent may be used, and the sizing agent is preferably composed of a coupling agent (e.g., a silane coupling agent), a lubricant, and a binder. The coupling agent can be selected to have good compatibility with the hydroxyl groups present on the surface of the carbon fibers, the binder can be selected to have good wettability with the selected thermoplastic resin or a surface tension similar thereto, and the lubricant can be selected to not interfere with the coupling agent and the binder. Examples of coupling agents suitable for use with carbon fibers include diamines such as 1,6-hexadiamine and polycarboxylic acids. The lubricant may be selected so as not to interfere with the coupling agent and the binder. The type of sizing agent used for the carbon fibers is not particularly limited, and any known sizing agent can be used. Specifically, for example, the one described in JP 2015-101794 A can be used.

[0054] (Shape of continuous reinforcing fibers) The continuous reinforcing fiber is a multifilament consisting of a plurality of filaments, and the number of single fibers is preferably 30 to 15,000 from the viewpoint of handling. The filament of the present embodiment may include a plurality of the multifilaments.

[0055] From the viewpoints of strength and handleability, the single filament diameter R of the continuous reinforcing fibers is preferably 2 to 30 μm, more preferably 4 to 25 μm, and even more preferably 6 to 20 μm.

[0056] Continuous reinforcing fiber single yarn diameter R (μm) and density D (g / cm 3 From the viewpoint of the ease of handling of the continuous reinforcing fibers and the strength of the composite material, the product RD is preferably 5 to 100 μm g / cm 3 , more preferably 10 to 50 μm g / cm 3 , and more preferably 15 to 45 μm g / cm 3 , and even more preferably 20 to 45 μm g / cm 3 It is.

[0057] The density D can be measured by a hydrometer. On the other hand, the single fiber diameter R (μm) is related to the density D (g / cm 3 ) and the number of single yarns (dtex), the following formula:

[0058]

number

[0059] In order to set the product RD of the continuous reinforcing fiber within a predetermined range, the fineness (dtex) and the number of single filaments (pieces) of commercially available continuous reinforcing fibers may be appropriately selected according to the density of the continuous reinforcing fibers. For example, when glass fibers are used as the continuous reinforcing fibers, the density of the glass fibers is about 2.5 g / cm 3 Therefore, it is sufficient to select one with a single filament diameter of 2 to 40 μm. Specifically, when the single filament diameter of the glass fiber is 9 μm, the RD will be 23 by selecting glass fiber with a fineness of 660 dtex and 400 single filaments. When the single filament diameter of the glass fiber is 17 μm, the RD will be 43 by selecting glass fiber with a fineness of 11,500 dtex and 2,000 single filaments. When carbon fiber is used as the continuous reinforcing fiber, the density is about 1.8 g / cm.3 Therefore, a carbon fiber with a single filament diameter of 2.8 to 55 μm should be selected. Specifically, when the single filament diameter of the carbon fiber is 7 μm, by selecting a carbon fiber with a fineness of 2,000 dtex and 3,000 single filaments, the product RD becomes 13. When aramid fiber is used as the continuous reinforcing fiber, the density is about 1.45 g / cm 3 Therefore, it is sufficient to select one with a single yarn diameter of 3.4 to 68 μm. Specifically, when the single yarn diameter of the aramid fiber is 12 μm, the product RD becomes 17 by selecting an aramid fiber with a fineness of 1,670 dtex and 1,000 single yarns.

[0060] Continuous reinforcing fibers, for example, glass fibers, are manufactured by measuring and mixing raw glass materials, molten glass in a melting furnace, spinning this into glass filaments, coating the filaments with a sizing agent, and passing the filaments through a spinning machine, and then winding them into direct wound rovings (DWR), cakes, twisted yarns, or other forms. The continuous reinforcing fibers may be in any form, but it is preferable to wind them into yarn, cake, or DWR, as this increases productivity and production stability in the resin coating process. From the viewpoint of productivity, DWR is the most preferable.

[0061] (thermoplastic resin) Thermoplastic resins contained in the filaments of this embodiment include, but are not limited to, polyolefin-based resins such as polyethylene and polypropylene; polyamide-based resins such as polyamide 6, polyamide 66, polyamide 46, polyamide 612, polyamide 6I, polyamide 610, polyamide 6I / 6T, polyamide 6T / 6I, polyamide 12, polyamide 4T, polyamide 6T, and polyamide 11; polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, and polytrimethylene terephthalate; polyacetal-based resins such as polyoxymethylene; polycarbonate-based resins; polyether-based resins such as polyether ketone, polyether ether ketone, polyether glycol, polypropylene glycol, and polytetramethylene ether glycol; polyether sulfone; polyphenylene sulfide; thermoplastic polyetherimide; thermoplastic fluorine-based resins such as tetrafluoroethylene-ethylene copolymers; polyurethane-based resins; acrylic resins, and modified thermoplastic resins obtained by modifying these. The thermoplastic resin may be used alone or as a mixture or copolymer of two or more kinds.

[0062] Among these thermoplastic resins, polyolefin resins, polyamide resins, polyester resins, polyether resins, polyethersulfone, polyphenylene sulfide, thermoplastic polyetherimide, and thermoplastic fluorine resins are preferred, polyolefin resins, modified polyolefin resins, polyamide resins, polyester resins, polyurethane resins, and acrylic resins are more preferred from the viewpoint of mechanical properties and versatility, and polyamide resins and polyester resins are even more preferred from the viewpoint of thermal properties. Furthermore, polyamide resins are even more preferred from the viewpoint of durability against repeated load loading.

[0063] -Polyester resin- The polyester resin refers to a polymer compound having an --CO--O-- (ester) bond in the main chain. Examples of polyester resins include, but are not limited to, polyethylene terephthalate, polybutylene terephthalate, polytetramethylene terephthalate, poly-1,4-cyclohexylene dimethylene terephthalate, and polyethylene-2,6-naphthalenedicarboxylate. The polyester resin may be a homopolyester or a copolymer polyester. In the case of copolymerized polyesters, those in which a homopolyester is copolymerized with an appropriate third component are preferred. Examples of the third component include, but are not limited to, diol components such as diethylene glycol, neopentyl glycol, and polyalkylene glycol, and dicarboxylic acid components such as adipic acid, sebacic acid, phthalic acid, isophthalic acid, and 5-sodium sulfoisophthalic acid. In addition, polyester-based resins using raw materials derived from biomass resources can also be used, and examples thereof include, but are not limited to, aliphatic polyester-based resins such as polylactic acid, polybutylene succinate, and polybutylene succinate adipate, and aromatic polyester-based resins such as polybutylene adipate terephthalate.

[0064] -Polyamide resin- The polyamide resin refers to a polymer compound having an -CO-NH- (amide) bond in the main chain. Examples include aliphatic polyamides, aromatic polyamides, and wholly aromatic polyamides.

[0065] Examples of polyamide-based resins include, but are not limited to, polyamides obtained by ring-opening polymerization of lactams, polyamides obtained by self-condensation of ω-aminocarboxylic acids, polyamides obtained by condensing diamines and dicarboxylic acids, and copolymers thereof. The polyamide resin may be used alone or in combination of two or more kinds. Examples of lactams include, but are not limited to, pyrrolidone, caprolactam, undecanelactam, and dodecalactam. Examples of ω-amino carboxylic acids include, but are not limited to, ω-amino fatty acids, which are ring-opened compounds of lactams with water. Two or more kinds of lactams or ω-amino carboxylic acids may be condensed together. Examples of diamines (monomers) include, but are not limited to, linear aliphatic diamines such as hexamethylenediamine and pentamethylenediamine; branched aliphatic diamines such as 2-methylpentanediamine and 2-ethylhexamethylenediamine; aromatic diamines such as p-phenylenediamine and m-phenylenediamine; and alicyclic diamines such as cyclohexanediamine, cyclopentanediamine, and cyclooctanediamine. Examples of dicarboxylic acids (monomers) include, but are not limited to, aliphatic dicarboxylic acids such as adipic acid, pimelic acid, and sebacic acid, aromatic dicarboxylic acids such as phthalic acid and isophthalic acid, and alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid. The diamines and dicarboxylic acids as monomers may each be condensed alone or in combination of two or more.

[0066] Examples of polyamide-based resins include, but are not limited to, aliphatic polyamides such as polyamide 4 (poly-α-pyrrolidone), polyamide 6 (polycaproamide), polyamide 11 (polyundecane amide), polyamide 12 (polydodecanamide), polyamide 46 (polytetramethylene adipamide), polyamide 66 (polyhexamethylene adipamide), polyamide 610, polyamide 612, and polyamide 1010; semi-aromatic polyamides such as polyamide 6T (polyhexamethylene terephthalamide), polyamide 9T (polynonamethylene terephthalamide), polyamide 6I (polyhexamethylene isophthalamide), polyamide MXD6, and polyamide 6I / 6T; and copolymer polyamides containing these as constituents. Examples of copolymerized polyamides include, but are not limited to, a copolymer of hexamethylene adipamide and hexamethylene terephthalamide, a copolymer of hexamethylene adipamide and hexamethylene isophthalamide, and a copolymer of hexamethylene terephthalamide and 2-methylpentanediamine terephthalamide.

[0067] [Additives] The filament of this embodiment may contain additives as necessary. The composite material of this embodiment may contain additives such as colorants, antioxidants, antioxidants, weathering agents, metal deactivators, light stabilizers, heat stabilizers, ultraviolet absorbers, antibacterial and antifungal agents, deodorizers, conductivity imparting agents, dispersants, softeners, plasticizers, crosslinking agents, co-crosslinking agents, vulcanizing agents, vulcanization assistants, foaming agents, foaming assistants, flame retardants, vibration dampers, nucleating agents, neutralizing agents, lubricants, antiblocking agents, dispersants, flow improvers, and mold release agents. The additives mentioned above are those excluding the above-mentioned components (for example, the thermoplastic resin, the continuous reinforcing fibers, the components contained in the thermoplastic resin composition for hybrids, and the components contained in the bundling agent). The content of the additive may be 3% by mass or less relative to 100% by mass of the composite material.

[0068] (Coloring agent) Examples of colorants include carbon black, nigrosine, aluminum pigments, titanium dioxide, ultramarine, cyanine blue, cyanine green, quinacridone, diatomaceous earth, monoazo salts, perylene, disazo, condensed azo, isoindoline, red iron oxide, nickel titanium yellow, diketone pyrrolopyrrole, metal salts, perylene red, metal oxides, bismuth vanadate, cobalt green, cobalt blue, anthraquinone, phthalocyanine green, phthalocyanine blue, etc. Among these, black colorants are preferred, and carbon black and nigrosine are more preferred.

[0069] The filament of this embodiment preferably has a continuous reinforcing fiber content of 90 to 525 parts by mass and other components of 0 to 2 parts by mass per 100 parts by mass of thermoplastic resin, and more preferably has a continuous reinforcing fiber content of 150 to 340 parts by mass and other components of 0 to 1 part by mass per 100 parts by mass of thermoplastic resin.

[0070] [Filament modeling] The filament of this embodiment can be used in various known additive manufacturing methods, and is particularly suitable for use in additive manufacturing.

[0071] [Uses of filament] The filament of the present embodiment can be suitably used for rockets, artificial satellites, aircraft, drones, braces, assist suits, wearable devices and other wearable members and devices, sporting goods such as soles, rackets, and fishing tackle, infrastructure such as utility poles, electric wires, and underground trenches, cars, construction materials, robots, electrical and electronic parts, various containers, daily necessities, household goods, sanitary products, tools, jigs, cases, and the like.

[0072] In automotive applications, the material can be used in, but is not limited to, the chassis / frame, undercarriage, drivetrain parts, interior parts, exterior parts, functional parts, and other parts. Specifically, steering shafts, mounts, sunroofs, steps, suspension trim, door trim, trunks, boot lids, bonnets, seat frames, seat backs, retractors, retractor support brackets, clutches, gears, pulleys, cams, argons, elastic beams, baffling, lamps, reflectors, glazing, front end modules, back door inners, brake pedals, handles, electrical materials, sound absorbing materials, door exteriors, interior panels, instrument panels, rear gates, ceiling ridges, seats, seat frames, wiper pillars, EPS (Electric Power Steering), small motors, heat sinks, ECU (Engine Control Unit) boxes, ECU housings, steering gear box housings, plastic housings, EV (Electric Vehicle motor housings, wire harnesses, on-board meters, combination switches, small motors, springs, dampers, wheels, wheel covers, frames, subframes, side frames, motorcycle frames, fuel tanks, oil pans, intake manifolds, propeller shafts, drive motors, monocoques, hydrogen tanks, fuel cell electrodes, panels, floor panels, exterior panels, doors, cabins, roofs, hoods, valves, EGR (Exhaust GasRecirculation valves, variable valve timing units, connecting rods, cylinder bores, members (engine mountings, front floor cloths, footwell cloths, seat cloths, inner sides, rear cloths, suspensions, pillar reinforcement, front sides, front panels, uppers, dash panel cloths, steering), tunnels, fastening inserts, crash boxes, crash rails, corrugated panels, roof rails, upper bodies, side rails, braiding, door surround assemblies, airbag parts, body pillars, dash-to-pillar gussets, suspension towers, bumpers, body pillar lowers, front body pillars, reinforcements (instrument panels, rails, roofs, front body pillars, roof rails, roof side rails, lockers, door belt lines, front floor unders, front body pillar uppers, front body pillar lowers, centre pillars, centre pillar hinges, door outside panels), side outer panels, front door window frames, MICS (Minimum Intrusion CabinSystem) bulk, torque box, radiator support, radiator fan, water pump, fuel pump, electronically controlled throttle body, engine control ECU, starter, alternator, manifold, transmission, clutch, dash panel, dash panel insulator pad, door side impact protection beam, bumper beam, door beam, bulkhead, outer pad, inner pad, rear seat rod, door panel, door trim board sub-assembly, energy absorber (bumper, shock absorbing), shock absorber, shock absorbing garnish, pillar garnish, roof side inner garnish, resin rib, side rail front spacer, side rail rear spacer, seat belt pretensioner, airbag They can be suitably used as parts for sensors, arms (suspension, lower, hood hinges), suspension links, shock absorbing brackets, fender brackets, inverter brackets, inverter modules, hood inner panels, hood panels, cowl louvers, cowl top outer front panels, cowl top outer panels, floor silencers, dump seats, hood insulators, fender side panel protectors, cowl insulators, cowl top ventilator loopers, cylinder head covers, tire deflectors, fender supports, strut tower bars, transmission center tunnels, floor tunnels, radio core supports, luggage panels, luggage floors, accelerator pedals, accelerator pedal bases, and the like. EXAMPLES

[0073] The present invention will be specifically described below with reference to examples and comparative examples. However, the present invention is not limited to these examples, and it goes without saying that the present invention can be practiced with various modifications within the scope of the gist of the present invention.

[0074] [Continuous reinforcing fiber folding degree Ff] The filament was cut to a length of 20 mm and attached to an acrylic plate measuring 5 mm square and 20 mm long. The acrylic plate was then placed on the flat surface of the glass plate so that the length direction of the acrylic plate was perpendicular to the flat surface of the glass plate, and fixed with double-sided tape. After that, an acrylic pipe measuring 14 mm in diameter and 20 mm in length was placed on the flat surface of the glass plate, surrounding the acrylic plate so that the acrylic plate was the center (axis) of the acrylic pipe. An embedding resin (epoxy resin) was injected into the acrylic pipe while preventing air from entering, and then hardened. Then, the cross section perpendicular to the longitudinal direction of the filament was exposed by polishing the polished surface with a polishing machine (IS-POLISHER ISPP-1000, manufactured by Ikegami Seiki Co., Ltd.) at 130 g / cm. 2 The cross section was exposed by polishing under the following conditions: 5 minutes with waterproof paper #400, 10 minutes with waterproof paper #2000, 5 minutes with silicon carbide film grain size 9 μm, 5 minutes with alumina film grain size 5 μm, and 5 minutes with alumina film grain size 3 μm so that a force of 1000 μm was applied. The obtained cross section was observed and photographed with a microscope (digital microscope VHX-5000, manufactured by Keyence Corporation) at a magnification of 300 times. In the obtained image, the smallest circle that could contain all of the continuous reinforcing fibers was drawn, and the distance l between each point on the circumference of the circle and the closest continuous reinforcing fiber from each point was measured. The longest l was taken as L, and the ratio ff of L to the length R of the diameter of the circle was calculated from the following formula (1). ff=L / R (1) ff was calculated at five random cross sections, and the average value was taken as Ff.

[0075] [Fiber volume fraction Vf] 0.5 g of the filament was placed in a crucible and then placed in an electric furnace and heated at 500°C for 1 hour to burn off the resin. After that, it was naturally cooled to room temperature, and the mass of the remaining reinforcing fiber was measured to determine the mass of the reinforcing fiber and resin contained in the filament. The obtained mass of the reinforcing fiber and the mass of the resin were converted to volume by dividing them by their respective densities, and the volume ratio of the reinforcing fiber to the filament (fiber volume content Vf) (%) was calculated.

[0076] [Continuous reinforcing fiber dispersion coefficient Fd] The filament was cut to a length of 20 mm and attached to an acrylic plate measuring 5 mm square and 20 mm long. The acrylic plate was then placed on the flat surface of the glass plate so that the length direction of the acrylic plate was perpendicular to the flat surface of the glass plate, and fixed with double-sided tape. After that, an acrylic pipe measuring 14 mm in diameter and 20 mm in length was placed on the flat surface of the glass plate, surrounding the acrylic plate so that the acrylic plate was the center (axis) of the acrylic pipe. An embedding resin (epoxy resin) was injected into the acrylic pipe while preventing air from entering, and then hardened. Then, the cross section perpendicular to the longitudinal direction of the filament was exposed by polishing the polished surface with a polishing machine (IS-POLISHER ISPP-1000, manufactured by Ikegami Seiki Co., Ltd.) at 130 g / cm. 2 The cross section was exposed by polishing under the following conditions: 5 minutes with waterproof paper #400, 10 minutes with waterproof paper #2000, 5 minutes with silicon carbide film grain size 9 μm, 5 minutes with alumina film grain size 5 μm, and 5 minutes with alumina film grain size 3 μm so that a force of 1000 μm was applied. The obtained cross section was observed and photographed with a microscope (digital microscope VHX-5000, manufactured by Keyence Corporation) at a magnification of 300 times. In the obtained image, the smallest circle that could contain all the continuous reinforcing fibers was drawn, and the diameter that crossed the continuous reinforcing fiber bundle the most was determined. The diameter that crossed the continuous reinforcing fiber bundle the most was taken as fd, the number of times it crossed the continuous reinforcing fiber bundle. fd was calculated for 20 arbitrary cross sections, and the average value was taken as Fd (times).

[0077] [Width of continuous reinforcing fiber bundle, fiber diameter of continuous reinforcing fiber, length of continuous reinforcing fiber bundle] The filament was cut to a length of 20 mm and attached to an acrylic plate measuring 5 mm square and 20 mm long. The acrylic plate was then placed on the flat surface of the glass plate so that the length direction of the acrylic plate was perpendicular to the flat surface of the glass plate, and fixed with double-sided tape. After that, an acrylic pipe measuring 14 mm in diameter and 20 mm in length was placed on the flat surface of the glass plate, surrounding the acrylic plate so that the acrylic plate was the center (axis) of the acrylic pipe. An embedding resin (epoxy resin) was injected into the acrylic pipe while preventing air from entering, and then hardened. Then, the cross section perpendicular to the longitudinal direction of the filament was exposed by polishing the polished surface with a polishing machine (IS-POLISHER ISPP-1000, manufactured by Ikegami Seiki Co., Ltd.) at 130 g / cm. 2 The cross section was exposed by polishing under the following conditions: 5 minutes with waterproof paper #400, 10 minutes with waterproof paper #2000, 5 minutes with silicon carbide film grain size 9 μm, 5 minutes with alumina film grain size 5 μm, and 5 minutes with alumina film grain size 3 μm so that a force of 1000 μm was applied. The obtained cross section was observed and photographed with a microscope (digital microscope VHX-5000, manufactured by Keyence Corporation) at a magnification of 300 times. In the obtained image, the width (μm) of the continuous reinforcing fiber bundle was calculated by measuring the distance between each point and the other point where the perpendicular line of each point intersected with the outline of the continuous reinforcing fiber bundle at 20 arbitrary points (points dividing the outline into 19 points of approximately equal length) on the outline of the continuous reinforcing fiber bundle, and calculating the average value of the measured values. In addition, the fiber diameter (μm) of the continuous reinforcing fiber was calculated from the obtained image as the average value of 20 arbitrary fibers. Further, from the obtained image, half the length of the outline of the continuous reinforcing fiber bundle was determined as the length (μm) of the continuous reinforcing fiber bundle. The values ​​obtained for any five cross sections were averaged to obtain the width of the continuous reinforcing fiber bundle of the filament, the fiber diameter of the continuous reinforcing fiber, and the length of the continuous reinforcing fiber bundle.

[0078] [Impregnation rate] The filament was cut to a length of 20 mm and attached to an acrylic plate measuring 5 mm square and 20 mm long. The acrylic plate was then placed on the flat surface of the glass plate so that the length direction of the acrylic plate was perpendicular to the flat surface of the glass plate, and fixed with double-sided tape. After that, an acrylic pipe measuring 14 mm in diameter and 20 mm in length was placed on the flat surface of the glass plate, surrounding the acrylic plate so that the acrylic plate was the center (axis) of the acrylic pipe. An embedding resin (epoxy resin) was injected into the acrylic pipe while preventing air from entering, and then hardened. Then, the cross section perpendicular to the longitudinal direction of the filament was exposed by polishing the polished surface with a polishing machine (IS-POLISHER ISPP-1000, manufactured by Ikegami Seiki Co., Ltd.) at 130 g / cm. 2 The cross section was exposed by polishing under the following conditions: 5 minutes with waterproof paper #400, 10 minutes with waterproof paper #2000, 5 minutes with silicon carbide film grain size 9 μm, 5 minutes with alumina film grain size 5 μm, and 5 minutes with alumina film grain size 3 μm so that a force of 1000 μm was applied. The obtained cross section was observed and photographed with a microscope (digital microscope VHX-5000, manufactured by Keyence Corporation) at a magnification of 300 times. In the obtained image, the area of ​​the region surrounded by the outline of the continuous reinforcing fiber bundle and the area of ​​the voids contained in the region surrounded by the outline of the continuous reinforcing fiber bundle were obtained, and the impregnation rate was calculated by the following formula. Impregnation rate (%) = {1-(area of ​​voids / area of ​​area enclosed by the outline of continuous reinforcing fiber bundle)} x 100 The impregnation rate was calculated for the five cross sections, and the average value was taken as the impregnation rate (%) of the filament.

[0079] [Flexural strength] Using a 3D printer (Mark2, manufactured by Markforged), a rectangular test piece with a length of 100 mm, a width of 10 mm, and a thickness of 2 mm was formed at an environmental temperature of 23 ° C. The test piece was composed of a total of 16 layers, with four layers from the upper and lower ends being formed with matrix filaments (Onyx, manufactured by Markforged), and the inner eight layers being formed with continuous fiber filaments obtained in each Example and Comparative Example. After drying the test piece in a vacuum dryer at 80 ° C. for 18 hours or more, the bending strength (MPa) was measured in an Instron universal testing machine at a speed of 1 mm / min, a span of thickness × 16 (mm), and an average value of five samples was obtained.

[0080] [Formability] Using a 3D printer (Mark2, Markforged), a cube with a length of 50 mm, width of 50 mm, and height of 50 mm was printed at an ambient temperature of 23°C. The cube was made up of a total of 400 layers, with four layers from each of the top and bottom ends printed with matrix filaments (Onyx, Markforged), and the remaining inner layers printed with the continuous fiber filaments obtained in each of the Examples and Comparative Examples. At this time, the number of times the continuous reinforcing fiber filaments clogged the nozzle was measured, and it was evaluated that the fewer the number of cloggings, the better the printability.

[0081] [Modeling precision] A 3D printer (Mark2, Markforged) was used to print a cube with a length of 50 mm, width of 50 mm, and thickness of 50 mm at an ambient temperature of 23°C. The cube was made up of a total of 400 layers, with four layers from each of the top and bottom ends printed with matrix filaments (Onyx, Markforged), and the remaining inner layers printed with continuous fiber filament layers obtained in each of the Examples and Comparative Examples. The length a (mm) of the obtained cube was measured, and the value of a / 50 was calculated. It was evaluated that the closer the obtained value was to 1, the better the printing accuracy.

[0082] [SP value] The SP value was calculated from the structure of each of the resin and continuous reinforcing fiber surface treatment agent components used in each Example and Comparative Example using the following formula. The evaporation energy and molar volume were referenced to values ​​obtained by the Fedors method. When multiple types of components were present, the SP value was calculated by the sum of the values ​​obtained by multiplying the mass ratio of the components by the SP value. (SP value) = {(total vaporization energy of atoms or atomic groups contained in each component) / (molar volume of atoms or atomic groups contained in each component)}^(1 / 2)

[0083] The materials used in the examples and comparative examples are as follows.

[0084] [Continuous reinforcing fiber] (Glass fiber) A glass fiber having a fineness of 68 tex and 700 single yarns was produced by attaching 0.45% by mass of the surface treatment agent to 100% by mass of the glass fiber. The winding form was DWR, and the average single yarn diameter was about 9 μm. The surface treatment agent was prepared by mixing 0.5% by mass of γ-aminopropyltriethoxysilane (KBE-903, manufactured by Shin-Etsu Chemical Co., Ltd.) as a coupling agent, 1% by mass of carnauba wax as a lubricant, 2% by mass of polyamide 6 resin as a binder, and 2.8% by mass of a copolymer compound (a copolymer compound having a weight average molecular weight of 20,000, obtained by copolymerizing 18% by mass of maleic anhydride, 57% by mass of methyl acrylate, and 25% by mass of methyl methacrylate) with deionized water. The SP value of the surface treatment agent was 12.5. (Carbon Fiber) Carbon fiber 1: 100% by mass of carbon fiber with 1000 single fibers, 7 μm diameter, and 69 tex fineness was produced by attaching 0.45% by mass of surface treatment agent to the carbon fiber. The surface treatment agent was prepared by mixing 1% by mass of carnauba wax as a lubricant, 2% by mass of polyamide 6 resin as a binder, and 2.8% by mass of a copolymer compound (a copolymer compound having a weight average molecular weight of 20,000, obtained by copolymerizing 18% by mass of maleic anhydride, 57% by mass of methyl acrylate, and 25% by mass of methyl methacrylate) with deionized water. The SP value of the surface treatment agent was 12.5. Carbon fiber 2: 100% by mass of carbon fiber with 1000 single fibers, 7 μm diameter, and 69 tex fineness was prepared by attaching 0.45% by mass of surface treatment agent to the 100% by mass of carbon fiber. The surface treatment agent was prepared by mixing 1% by mass of carnauba wax as a lubricant, 3% by mass of polypropylene resin as a binder, and 1.8% by mass of a copolymer compound (a copolymer compound having a weight average molecular weight of 20,000, obtained by copolymerizing 22% by mass of maleic anhydride, 45% by mass of methyl acrylate, and 33% by mass of methyl methacrylate) with deionized water. The SP value of the surface treatment agent was 9.8. Carbon fiber 3: 100% by mass of carbon fiber with 1000 single fibers, 7 μm diameter, and 69 tex fineness was prepared by attaching 0.45% by mass of surface treatment agent to the 100% by mass of carbon fiber. The surface treatment agent was prepared by mixing 1% by mass of carnauba wax as a lubricant, 2% by mass of polyamide 6 resin as a binder, and 2.8% by mass of a copolymer compound (a copolymer compound having a weight average molecular weight of 20,000, obtained by copolymerizing 12.5% ​​by mass of maleic anhydride, 59.4% by mass of methyl acrylate, and 28.1% by mass of methyl methacrylate) with deionized water. The SP value of the surface treatment agent was 12.2.

[0085] [Thermoplastic resin] Resin 1: Polyamide 66 (SP value: 12.4) Resin 2: Compound of Resin 1 and Polyamide 6I (PA66:PA6I=65:35) (SP value: 12.5) Resin 3: Polyamide 6 (SP value: 12.3) Resin 4: Polyphenylene sulfide (SP value: 11.7) Resin 5: Modified polyphenylene ether (PPE:PS=65:35, SP value: 9.6) Resin 6: Compound of Resin 1 and polyphenylene ether (PA66:PPE=88:12, SP value: 12.0) Resin 7: Compound of Resin 1 and polyphenylene ether (PA66:PPE=68:32, SP value: 11.4) Resin 8: Compound of Resin 1 and polyphenylene ether (PA66:PPE=53:47, SP value: 11.0) Resin 9: Polypropylene (SP value: 8.4)

[0086] [Example 1] A filament was produced using resin 1 and glass fiber. An extruder (Filabot EX2, manufactured by Filabot) was fitted with a nozzle having a hollow section with an inner diameter of 5 mm and a length of 15 cm, and a hole of Φ0.35 mm at the tip. The resin extruded from the extruder was filled into the hollow section (cavity) of this nozzle. In addition, a cylindrical die was attached to the nozzle, and glass fiber was passed through the holes of the die and nozzle. The extrusion temperature and die temperature were set to 270°C, and the resin 1 and glass fiber extruded from the die were wound up to obtain a filament (120 m). The viscosity of resin 1 was 350 g / 10 min during filament production. The measurement and evaluation results of each physical property are shown in Table 1.

[0087] [Example 2] A filament was obtained in the same manner as in Example 1, except that Resin 2 was used as the thermoplastic resin. When the filament was produced, the viscosity of Resin 2 was 250 g / 10 min. The measurement and evaluation results of each physical property are shown in Table 1.

[0088] [Example 3] A filament was obtained in the same manner as in Example 1, except that carbon fiber 1 was used as the continuous reinforcing fiber. When the filament was produced, the viscosity of resin 1 was 350 g / 10 min. The measurement and evaluation results of each physical property are shown in Table 1.

[0089] [Example 4] A filament was obtained in the same manner as in Example 3, except that Resin 2 was used as the thermoplastic resin. When the filament was produced, the viscosity of Resin 2 was 250 g / 10 min. The measurement and evaluation results of each physical property are shown in Table 1.

[0090] [Example 5] A filament was obtained in the same manner as in Example 3, except that Resin 3 was used as the thermoplastic resin. When the filament was produced, the viscosity of Resin 3 was 540 g / 10 min. The measurement and evaluation results of each physical property are shown in Table 1.

[0091] [Example 6] A filament was obtained in the same manner as in Example 3, except that Resin 4 was used as the thermoplastic resin and the extrusion temperature and die temperature were set to 320° C. When the filament was produced, Resin 4 had a viscosity of 30 g / 10 min. The measurement and evaluation results of each physical property are shown in Table 1.

[0092] [Example 7] A filament was obtained in the same manner as in Example 1, except that Resin 5 was used as the thermoplastic resin and Carbon Fiber 2 was used as the continuous reinforcing fiber. When the filament was produced, the viscosity of Resin 5 was 50 g / 10 min. The measurement and evaluation results of each physical property are shown in Table 1.

[0093] [Example 8] A filament was obtained in the same manner as in Example 3, except that Resin 6 was used as the thermoplastic resin. When the filament was produced, Resin 6 had a viscosity of 8 g / 10 min. The measurement and evaluation results of each physical property are shown in Table 1.

[0094] [Example 9] A filament was obtained in the same manner as in Example 3, except that Resin 7 was used as the thermoplastic resin. When the filament was produced, Resin 7 had a viscosity of 7 g / 10 min. The measurement and evaluation results of each physical property are shown in Table 1.

[0095] [Example 10] A filament was obtained in the same manner as in Example 3, except that Resin 8 was used as the thermoplastic resin. When the filament was produced, Resin 8 had a viscosity of 7 g / 10 min. The measurement and evaluation results of each physical property are shown in Table 1.

[0096] [Example 11] A filament was obtained in the same manner as in Example 3, except that Resin 4 was used as the thermoplastic resin and Carbon Fiber 3 was used as the continuous reinforcing fiber. When the filament was produced, the viscosity of Resin 4 was 30 g / 10 min. The measurement and evaluation results of each physical property are shown in Table 1.

[0097] [Comparative Example 1] A filament was obtained in the same manner as in Example 1, except that Resin 9 was used as the thermoplastic resin. When the filament was produced, Resin 9 had a viscosity of 1240 g / 10 min. The measurement and evaluation results of each physical property are shown in Table 1.

[0098] [Comparative Example 2] A filament was obtained in the same manner as in Example 3, except that Resin 9 was used as the thermoplastic resin. When the filament was produced, the viscosity of Resin 9 was 1240 g / 10 min. The measurement and evaluation results of each physical property are shown in Table 1.

[0099] [Comparative Example 3] A filament was obtained in the same manner as in Example 7, except that Resin 1 was used as the thermoplastic resin. When the filament was produced, the viscosity of Resin 1 was 350 g / 10 min. The measurement and evaluation results of each physical property are shown in Table 1.

[0100] [Table 1] [Industrial Applicability]

[0101] The filament of this embodiment can be used industrially as a reinforcing material for materials that require high levels of mechanical properties, such as structural parts for various transportation equipment and automobiles, and as a composite molding material with a thermoplastic resin composition.

Claims

1. A filament for additive manufacturing comprising continuous reinforcing fibers and a thermoplastic resin, characterized in that the continuous reinforcing fiber folding degree (Ff) obtained by the following steps (a) to (f) is 0.50 or less, and in a cross section perpendicular to the longitudinal direction of the filament, 60% or more of the continuous reinforcing fibers are gathered to form a continuous reinforcing fiber bundle. (a) The filament is embedded in a resin, and a cross section perpendicular to the longitudinal direction is exposed by polishing. (b) An image of the cross section is taken using a microscope. (c) In the obtained image, the smallest circle that contains all of the continuous reinforcing fibers is drawn. (d) Measure the distance l between each point on the circumference of the circle and the continuous reinforcing fiber closest to each point, and define the longest distance l as L. (e) The ratio ff of the length L to the diameter R of the circle is calculated using the following formula (1). ff=L / R (1) (f) ff is calculated for any 20 cross sections, and the average value is taken as Ff.

2. The filament according to claim 1, wherein the maximum value of ff of the 20 cross sections is 0.50 or less.

3. The filament according to claim 1 or 2, wherein the fiber volume content of the filament is 5 to 50%.

4. The filament according to claim 1, wherein the continuous reinforcing fiber dispersion coefficient (Fd) calculated by the following steps (A) to (F) is 3 times or less. (A) The filament is embedded in a resin, and a cross section perpendicular to the longitudinal direction is exposed by polishing. (B) An image of the cross section is taken using a microscope. (C) In the obtained image, the smallest circle that contains all of the continuous reinforcing fibers is drawn. (D) Among the diameters of the circles, the diameter that crosses the continuous reinforcing fiber bundle the greatest number of times is determined. (E) The number of times that the diameter that crosses the continuous reinforcing fiber bundle the most crosses the continuous reinforcing fiber bundle is defined as fd. (F)fd is determined for any 20 cross sections, and the average value is taken as Fd.

5. The filament according to claim 1, 2, or 4, wherein in the cross section, the width of the continuous reinforcing fiber bundle is 3 to 20 times the fiber diameter of the continuous reinforcing fiber.

6. 5. The filament of claim 1, 2, or 4, wherein in the cross section, the length of the continuous reinforcing fiber bundle is three times or more the width of the continuous reinforcing fiber bundle.

7. The filament according to claim 1 , 2 or 4 , wherein the continuous reinforcing fiber contains a surface treatment agent, and the difference in SP value between the thermoplastic resin and the surface treatment agent of the continuous reinforcing fiber is 1.0 or less.

8. A method for producing the filament according to claim 1, comprising the steps of: treating the continuous reinforcing fibers with a surface treatment agent to produce continuous reinforcing fibers that include a surface treatment agent; The method for producing a filament, wherein the difference in SP value between the surface treatment agent for the continuous reinforcing fiber and the thermoplastic resin is 1.0 or less.

Citation Information

Patent Citations

  • Additive manufacturing compositions

    WO2019195694A1

  • Fiber-reinforced thermoplastic resin filament for 3D printer, and molded article thereof

    WO2020217929A1